Swaying citizen support for EU membership: Evidence from a survey experiment of German voters. (September 2020) - Yordanova, Nikoleta; Angelova, Mariyana; Lehrer, Roni; Osnabrügge, Moritz; Renes, Sander
The United Kingdom's 2016 'Brexit' referendum vote to leave the European Union (EU) raised concerns that other countries would follow suit. This article examines how arguments about EU membership related to economic, cultural, political, and security and peace issues could influence how citizens would vote in EU membership referendums. Our two-wave survey experiment on a random sample of the German population and difference-in-differences analysis revealed that only fears of being outvoted in EU decision-making swayed German voters' attitudes about EU membership, particularly voters with weaker EU support, little EU knowledge and low levels of political engagement. We therefore conclude that concerns about sovereignty loss can be drivers of Euroscepticism even in a country that has vast influence over EU decisions.